GENDER EQUALITY AS A LEGAL PRINCIPLE - Tuxtasinov Shoxruxxon Ne’matjon o’g’li (Scholar Express Journal, 2023)
The description of gender equality as the value of law in discourse of anthropological tendency is given in the article. Considered right to differences in the aspect of gender mainstreaming in law. The main components of gender equality are characterized.
Keywords: Sex; gender; right to differences; gender mainstreaming